Analisa Pendapatan Mudharabah Terhadap Profitabiltas Koperasi BMT-Maslahah Sidogiri Cabang Sukorejo - Abdillah Mundir; Muhammad Saidi (ICO EDUSHA, 2022)
Based on the details of data above, the authors determine the focus of the research problem, determine how the techniques and income of Mudharabah Muqayyadah in the Sidogiri BMT-Maslahah Cooperative how the techniques and income of Mudharabah Muqayyadah in the Sidogriri BMT-Maslahah profitability of the BMT-Maslahah Cooperative.  The purpose of this study was to determine the techinques and income of Mudharabah Muqayyadah in the BMT-Maslahah Sidogiri Cooperative, to determine the techniques and income of Mudharabah Muqayyadah in the Maslahah Sidogiri BMT Maslahah Sidogiri Cooperativ and to determine the income of Mudharabah Muqayyadah in Increasing the profitability of the BMT-Maslahah. Cooperative this research method is a quantitative type using descriptive problem formulation approach. Based of the results of the discussion here are the BMT-Maslahah sukorejo branch is controlling the goals, vision, mission, and thought in a harmony with ecah other. BMT-Maslahah team sukorejo branch. BMT-Maslahah sidogiri income Sukorejo branch hit the target. Keywords: BMT, Income, Mudharabah, profitability     References Akerta, Alfindo, and Hasan Bisri. “Pengaruh Pendapatan Bagi Hasil Mudharabah Dan Pendapatan Margin Murabahah Terhadap Laba Perusahaan Di PT. Bank Syariah Bukopin Periode 2013-2016.” jurnal artikel 3, no. 1 (2019): 105. http://jurnal.unma.ac.id/index.php/Mr/index%0Aberganda. Alfiah Syahrinawati. “Peran Bmt ( Baitul Mal Wat Tamwiil) Dalam Mengembangkan Pembiayaan Usaha Mikro Kecil Menengah Pada Bmt Ugt Sidogiri Cabang Malang.” jurnal artikel (2021): 1–2. Amir Mu’allim. “Pratek Pembiayaan Bank Syariah Dan Problematikanya.” jurnal artikel 7 (2013): 49. Ilyas, Rahmat. “Konsep Pembiayaan Dalam Perbankan Syari’ah.” Jurnal Penelitian 9, no. 1 (2015): 183–204. Isrososiawan, Safroni. “Pengaruh Pengembangan Usaha Koperasi Terhadap Peningkatan Sisa Hasil Usaha Pada Koperasi Pegawai Republik Indonesia (Kpri) Iain Mataram.” Jurnal Pendidikan Ekonomi (2014): 28–30. Khoirunnisa, Ervina. “Penerapan Pelayanan Sistem Jemput Bola Pada Kspps Tamzis Bina Utama Kantor Cabang Kertek Wonosobo” 4, no. 1 (2019): 13. lifepal. “Nasabah – Pengertian, Jenis, Dan Keuntungannya.” Lifepal. Last modified 2021. Accessed July 23, 2021. https://lifepal.co.id/media/nasabah/. Mahbub, M.Ag. “Pengaruh Pembiayaan Mudharabah Terhadap Pendapatan BMT UGT Sidogiri Capem Songgon Kabupaten Banyuwangi.” jurnal artikel 2, no. 2 (2016): 63–80. Melina, Ficha. “Pembiayaan Murabahah Di Baitul Maal Wat Tamwil (Bmt).” jurnal artikel 3, no. 2 (2020): 269–280. Pabundu, Tika Moh. “Metodologi Riset Bisnis, Jakarta: PT.” Bumi Aksara, no. June (2006). Perekonomian, Kementrian. “Kementerian Koordinator Bidang Perekonomian.” Kementrian Perekonomian. Last modified 2022. Accessed June 20, 2022. https://ekon.go.id/. Soemitra, Andri. “Bank Dan Lembaga Keuangan Syariah.” In Book Section, 35–36. 1st ed. Jakarta: Prenada Media Group, 2009. Sugiyono. Metode Peneltian Kuantitatif & Kualitatif Dan R&D. Bandung: Alfabeta, 2012. Supriyanto, Oleh Dodi, and Dede A Ardiansah. “Analisis Pendapatan Mudharabah Muqayyadah Dan Non Performing Financing (Npf) Terhadap Profitabilitas (Roa).” jurnal artikel 6 (2016): 368. https://jurnal.unigal.ac.id/index.php/ekonologi. Ziqri, Muhamas. “Analisis Pengaruh Pendapatan Murabahah, Mudharabah Dan Musyarakah Terhadap Profitabilitas Bank.” Skripsi (2009): 1–133. http://repository.uinjkt.ac.id/dspace/handle/123456789/1328.